Dynamic physiological response of tef to contrasting water availabilities - Alemu, Muluken Demelie; Barak, Vered; Shenhar, Itamar; Batat, Dor; Saranga, Yehoshua (Frontiers in Plant Science, 2024)
Global climate change is leading to increased frequency of extreme climatic events, higher temperatures and water scarcity. Tef (Eragrostis tef (Zucc.) Trotter) is an underutilized C4 cereal crop that harbors a rich gene pool for stress resilience and nutritional quality. Despite gaining increasing attention as an "opportunity" crop, physiological responses and adaptive mechanisms of tef to drought stress have not been sufficiently investigated. This study was aimed to characterize the dynamic physiological responses of tef to drought. Six selected tef genotypes were subjected to high-throughput whole-plant functional phenotyping to assess multiple physiological responses to contrasting water regimes. Drought stress led to a substantial reduction in total, shoot and root dry weights, by 59%, 62% and 44%, respectively (averaged across genotypes), and an increase of 50% in the root-to-shoot ratio, relative to control conditionstreatment. Drought treatment induced also significant reductions in stomatal conductance, transpiration, osmotic potential and water-use efficiency, increased chlorophyll content and delayed heading. Tef genotypes exhibited also variations in most variables and exhibited diverse water-use strategies under drought: water-conserving (isohydric) or non-conserving (anisohydric), or an intermediate strategy, as well as in drought-recovery rate. Genotype RTC-290b exhibited outstanding multifaceted drought-adaptive performance, including high water-use efficiency coupled with high productivity under drought and control treatments, high chlorophyll and transpiration under drought, and faster drought recovery rate. Notably, a significant association was found between drought responses (relative total dry weight) in this high-throughput and our previous field study.This study provides a first insight into the dynamic functional physiological responses of tef to water deficiency and the variation between genotypes in drought-adaptive strategies. These results may serve as a baseline for further studies and for the development of drought-resistant tef varieties.